Active LXR signaling, coupled with elevated mitochondrial and glycolytic metabolism contributes to GM-CSF–induced trained immunity - Liu, Yuanyuan; Hamid, Arslan; Hardege, Hannah; Zhang, Qian; Körner, Helena; Leffers, Merle; Gonzalez, Noelia A.; Liebisch, Gerhard; Hoering, Marcus; Findeisen, Hannes; Placek, Katarzyna; Netea, Mihai G.; et al. (Frontiers in Immunology, 2026)
Granulocyte-macrophage colony-stimulating factor (GM-CSF) contributes to the host defense and the pathogenesis of inflammatory diseases at least in part through inducing trained immunity (TI), however, the mechanism remains poorly characterized. In this paper, we systematically investigated the associated metabolic and epigenetic reprogramming, with a particular focus on the role of liver X receptors (LXRs) in this process. We employed a comprehensive experimental approach, including in vitro isolation and purification of human monocytes from healthy donors, cytokine assays, quantitative PCR, Seahorse metabolic analysis, flow cytometry, and chromatin immunoprecipitation (ChIP), shotgun lipidomics, as well as transcriptomic data analysis to investigate GM-CSF–induced trained immunity. Our results demonstrate that GM-CSF induces TI by enhancing cellular metabolism, as evidenced by increased glycolysis, mitochondrial activity, fatty acid oxidation, and pyruvate metabolism. Lipidomics and RNA sequencing analyses revealed upregulation of lipid synthesis, high triglyceride storage, and acetyl-CoA–producing pathways, leading to increased histone acetylation in GM-CSF–trained cells. Furthermore, glycolysis and mitochondrial metabolism are essential for establishing TI in these cells. Notably, pharmacological inhibition of GM-CSF activated LXR signaling, which potentially mediated via PPARγ, attenuated GM-CSF–induced TI via reducing glycolytic flux and histone acetylation while activation of LXR amplified these effects. Together, these results highlight the role of LXR in linking cellular metabolism with epigenetic reprogramming and demonstrate that elevated metabolic activity and active LXR signaling both are essential for GM-CSF–induced trained immunity. Importantly, these pathways may represent therapeutic targets for modulating GM-CSF–driven maladaptive inflammation in chronic inflammatory diseases.